Tunisia : First Review Under the Extended Fund Facility, Request for Waivers of NonObservance of Performance Criteria and Rephasing of Access-Press Release; Staff Report;and Statement by the Executive Director for Tunisia. (IMF Staff Country Reports; Country Report, 2017)
This paper discusses Tunisia's First Review Under the Extended Fund Facility (EFF), Request for Waivers of Nonobservance of Performance Criteria and Rephasing of Access. Most quantitative performance criteria (QPCs) for end-December 2016 were missed and all structural benchmarks (SBs) through March 2017 were delayed. Most delayed SBs, including on private sector legislation, performance contracts for public banks, the civil service strategy, and the large taxpayers unit are now completed. The remaining ones will be achieved by end-2017. The IMF staff recommends the completion of the EFF review and supports the authorities' request for rephasing of access and waivers of nonobservance of end-December QPCs.